Heterogeneity of risk within Gleason 4 + 4, 4 + 5 and 5 + 4 prostate cancer. (2nd November 2018) - Moschini, Marco; Sharma, Vidit; Soligo, Matteo; Psutka, Sarah; Rangel, Laureano; Boorjian, Stephen A.; Frank, Igor; Gettman, Matthew T.; Thompson, R. Houston; Tollefson, Matthew K.; Karnes, R. Jeffrey
Abstract: Objects: This study hypothesized that biopsy Gleason score 8 (b.G.S. 8) disease may dilute the substantial poor risk associated with b.G.S. 9 disease, specifically associated with primary Gleason 5 disease. Materials and methods: The study reviewed 18, 299 patients treated with radical prostatectomy (R.P.) between 1990 and 2011, and identified 1, 080 men with b.G.S. 4 + 4 ( n = 614, 56.9%), 4 + 5 ( n = 347, 32.1%), and 5 + 4 ( n = 119, 11%) P.Ca. Variation trends of high risk prostate cancer (H.R.P.Ca.) characteristics were recorded over time: The association of b.G.S. with survival outcomes was assessed using Kaplan Meier and multivariable Cox regression analyses. Median follow-up was 6.1 years (I.Q.R. = 3–10.8). Results: The number of patients included in H.R.P.Ca. due to their b.G.S. increased consistently over time. On multivariable regression, b.G.S. 4 + 5 and b.G.S. 5 + 4 vs b.G.S. 4 + 4 were found to be independently associated with seminal vesical involvement (Odds ratio [O.R.] = 1.58 and 2.22; p < 0.005), extracapsular extension (O.R. = 1.51 and 1.7; p < 0.02) and surgical margins (O.R. = 1.50 and 2.03; p < 0.01), respectively. Ten-year cancer-specific survival was 83%, 73% and 70% in patients with b.G.S. 4 + 4, 4 + 5 and 5 + 4, respectively ( p < 0.01). b.G.S. 4 + 5 and b.G.S. 5 + 4 compared to b.G.S. 4 + 4 were associated with an increased risk of cancer-specific mortality (C.S.M.) (Hazard ratio = 1.76, p = 0.02 and 2.38, p = 0.003, respectively). Conclusions: B.G.S. 9 and specifically pattern 5 + 4 P.Ca. is associated with substantial disease burden, adverse pathological features and the presence of locally advanced disease, in addition to inferior survival outcomes in comparison to b.G.S. 4 + 4 disease. Distinction of b.G.S. 9 patients from b.G.S. 8 patients at diagnosis may permit more precise pre-treatment risk stratification.